2012
DOI: 10.1111/j.1600-0625.2012.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of melanin synthesis by the antidepressant fluoxetine

Abstract: Fluoxetine, a member of the class of selective serotonin reuptake inhibitors, is a potent antidepressant commonly used in clinical practice. Here, we report that fluoxetine increases cellular tyrosinase (TYR) activity, enhances the protein levels of microphthalmia-associated transcription factor (MITF), TYR and tyrosinase-related protein-1 (TRP-1) and eventually leads to a dramatic increase in melanin production in both murine B16F10 melanoma cells and normal human melanocytes (NHMCs). In well-characterized C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
(16 reference statements)
0
22
0
Order By: Relevance
“…Emerging data also demonstrate that serotonin can be transported or released by skin cells [27]. In our previous study, it was found that FX could enhance melanogenesis in B16F10 cells and NHMCs [32]. We have now extended this initial study to examine 5-HT signaling in pigmentary responses related to stress and reveal novel functions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Emerging data also demonstrate that serotonin can be transported or released by skin cells [27]. In our previous study, it was found that FX could enhance melanogenesis in B16F10 cells and NHMCs [32]. We have now extended this initial study to examine 5-HT signaling in pigmentary responses related to stress and reveal novel functions.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, 5-HT induces melanogenesis via stimulation of 5-HT2R in SK-MEL-2 melanoma cells [31]. Fluoxetine (FX), a member of the class of selective serotonin reuptake inhibitors, can also lead to a dramatic increase in melanin production in both murine B16F10 cells and NHMCs [31], [32]. In vivo, 5-HT is also best known to have various roles in skin, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3 More recent studies also noted that serotonin agonist or fluoxetine treatment can induce melanogenesis. 4 These observations collectively might explain the cross-sensitivity of various SSRI with intrinsic activities to increase serotonin. In conclusion, clinicians should be aware of the shared risk or cross-sensitivity among SSRI to induce photosensitivity, and may consider switching to other antidepressants with different pharmacological mechanisms when this occurs.…”
mentioning
confidence: 94%
“…Rigorous review and analysis of the literature suggested that many commonly prescribed drugs, for example, selective serotonin reuptake inhibitor (SSRI) could cause temporary hair loss . At the same time, our previous study indicated that the antidepressant fluoxetine induces melanogenesis both in vitro and in vivo, and 5‐HTR1A is one of the involved pathways in the regulation of melanogenesis by fluoxetine in B16F10 cells . Researchers have revealed that stress could indeed inhibit hair growth in vivo, but the relationship between chronic stress and melanogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%